THE EFFECT OF DETERMINED TAX LOAD, TAX PLANNING AND MANAGERIAL OWNERSHIP ON PROFIT MANAGEMENT IN MANUFACTURING COMPANIES IN THE BASIC AND CHEMICAL INDUSTRY SECTOR LISTED ON IDX 2018-2020 - Nurdina Nurdina; R Yudi Sidharta; Faidatul Hasanah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The importance of implementing accounting policies in accordance with the provisions of the Statement of Financial Accounting Standards (PSAK) and tax rules without violating the provisions of the law can be carried out by taking into account deferred tax expense tax planning, managerial ownership in, earnings management. The population of this research is 77 industries in the lower industrial zones as well as chemicals listed on the IDX. The sample contained is 33 annual financial statements for the 2018-2020 period, with a selected sample of 11 companies. The sampling technique used is purposive sampling. The results of this observation explain that deferred tax expense and tax planning affect earnings management, while managerial ownership has no effect on earnings management.